Interruption of the expiry date to interpose the subjective action as a consequence of the interposition of a constitutional action - Moreta Neira, Andrés Sebastián (2022)
This paper challenges the widespread idea both among judges and the doctrine of an uninterrupted expiration period of a subjective action of full jurisdiction action, not even if constitutional guarantees are applied upon the same administrative act. This article analyzes National and Constitutional Court sentences that have already ruled against this possibility a protection appeal (recurso de amparo), a notion that could be confronted due to the legal nature of the protection appeal and the validity of the Organic Administrative Code (COA) that introduces new rules regarding the nullity of administrative acts. This research presents a hypothetic scenario: a favorable sentence obtained in the first instance through constitutional procedures is eventually revoked in second instance with no regard to the rules that norm the deadlines of that action. This would bring the deadline to attend the contentious administrative seat forward and the expiration implies an unnecessary barrier to a person affected by the act.